GC-MS Analysis of Methanol Extracts of Five Toxic Plant Seed For Detection of Bioactive Compounds (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present work was carried out to explore the qualitative analysis of bioactive phyto-constituents presentin methanolic extracts of five toxic plant seeds by using gas chromatography-mass spectrometry. Theanalysis of extracts revealed the presence of the different biologically active compounds including alkaloids,glycosides, flflavonoids, phenols, fatty acid, ester, epoxide, steroids, and protein etc. Forensic toxicologicalchemistry deals with the chemistry and analysis of various types of poisons including plants. Diagnosingplant poisoning especially their seeds can be difficult and must be quickly done. In conclusion, the recoveryof various toxic and therapeutically constituents could be helpful for forensic toxicologist.